2017
DOI: 10.1038/s41598-017-12186-w
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of an ASCH protein from Zymomonas mobilis and its ribonuclease activity specific for single-stranded RNA

Abstract: Activating signal cointegrator-1 homology (ASCH) domains were initially reported in human as a part of the ASC-1 transcriptional regulator, a component of a putative RNA-interacting protein complex; their presence has now been confirmed in a wide range of organisms. Here, we have determined the trigonal and monoclinic crystal structures of an ASCH domain-containing protein from Zymomonas mobilis (ZmASCH), and analyzed the structural determinants of its nucleic acid processing activity. The protein has a centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Sequence and structure analyses have shown that the EVE domain is a member of the PUA ( p seudo u ridine synthase and a rchaeosine transglycosylase)/ASCH ( ASC -1 h omology) superfamily, a widely disseminated and apparently ancient assemblage of nucleic acid-binding domains [ 8 13 ]. These domains are generally associated with the translation apparatus, often fused to RNA modification enzymes, and bind RNA themselves [ 11 14 ]. Some ASCH domains have also been predicted to bind modified bases [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sequence and structure analyses have shown that the EVE domain is a member of the PUA ( p seudo u ridine synthase and a rchaeosine transglycosylase)/ASCH ( ASC -1 h omology) superfamily, a widely disseminated and apparently ancient assemblage of nucleic acid-binding domains [ 8 13 ]. These domains are generally associated with the translation apparatus, often fused to RNA modification enzymes, and bind RNA themselves [ 11 14 ]. Some ASCH domains have also been predicted to bind modified bases [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the crystal structure of an ASCH domain-containing protein from Zymomonas mobilis (ZmASCH) has been determined revealing a ribonuclease activity. The detailed mechanism of RNA hydrolysis is yet to be elucidated, but it has been confirmed that three residues (Tyr47, Lys53, and Ser128) located in a cleft contribute to nucleic acid-binding and RNA cleavage 25 . However, the biological role Media and growth conditions.…”
Section: Yqfbmentioning
confidence: 99%
“…The amino acid sequence analysis using SMART [46] revealed that D8_RL contains the human activating signal cointegrator homology (ASCH) [47] and growth-arrest-specific protein 2 (GAS2) domains [48]. ASCH domain-containing proteins are widespread and diverse but, at present, the vast majority of those proteins have no function assigned to them [47], except for an ASCH domain-containing ribonuclease from Zymomonas mobilis [49] and a recently characterized unique ASCH domain-containing amidohydrolase YqfB from Escherichia coli, which is active towards N 4 -acylcytidines [50]. The comparison of YqfB and D8_RL amino acid sequences showed merely 17 identical residues between these two proteins, and only 2 of the 4 YqfB catalytic amino acids were among them, although the aspartic acid residue in position 72 of the D8_RL and the catalytic glutamic acid residue in position 74 of the YqfB enzyme can also be considered conservative ones (Figure 3 and Figure S2).…”
Section: Bioinformatic Analysis Of the Selected Clonesmentioning
confidence: 99%